International Scientific and Practical Conference "AgroSMART - Smart Solutions for Agriculture" (AgroSMART 2018) 2018
DOI: 10.2991/agrosmart-18.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Impervious Protection of Hydraulic Structures of Irrigation Systems

Abstract: To prolong the service life of hydraulic structures of irrigation systems and dams there were developed and patented method and device of creating impervious coating of irrigation channels, impervious geotextile coating of low-pressure earthen dams, a device for sealing butt joints of trays providing recovery of water conveyance constructions, operational reliability and durability of impervious coatings, elimination of filtration and leakage in water conveyance constructions. On channels, the result is achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Observations showed that the UWC of the temporary channel and the UWC of the section channel are close to each other [7,8].…”
Section: Practical and Scientific Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Observations showed that the UWC of the temporary channel and the UWC of the section channel are close to each other [7,8].…”
Section: Practical and Scientific Resultsmentioning
confidence: 82%
“…To further define the symbols "A" and "m" in the formula, it is necessary to observe in the calculation the numerical equality of each consumption symbol or consumption interval indicator with the experimental indicator. If the interval at one expenditure is greater than the experimental values but less for other intervals, they are taken into account in the calculation as an exception, and they are equalized at the expense of the auxiliary table [7][8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, one of the most significant challenges is the substantial loss of water within these irrigation canals, with filtration accounting for a substantial portion, often reaching up to 50% of the total water losses [2][3]. These losses incurred due to filtration in earthen canal systems have deleterious consequences, including canal area inundation, adjacent land swamping and flooding, salinization of the canal vicinity, and, in extreme cases, the cessation of canal functionality [4][5][6]. The extent of water loss attributed to filtration from these canals is contingent upon various factors, including the canal's specific parameters, the permeability characteristics of the underlying soil, the groundwater table elevation, among other variables [7].…”
Section: Introductionmentioning
confidence: 99%